2015
DOI: 10.1093/scan/nsv039
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and electro-cortical concomitants of social feedback processing in women

Abstract: This study provides a joint analysis of the cardiac and electro-cortical—early and late P3 and feedback-related negativity (FRN)—responses to social acceptance and rejection feedback. Twenty-five female participants performed on a social- and age-judgment control task, in which they received feedback with respect to their liking and age judgments, respectively. Consistent with previous reports, results revealed transient cardiac slowing to be selectively prolonged to unexpected social rejection feedback. Late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
44
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 57 publications
18
44
2
Order By: Relevance
“…Following the task, participants complete a self-report measure of task engagement. Our initial pilot study ( N = 19) indicated that an enhanced RewP was observable following social acceptance feedback, a pattern that has also been observed in adult studies of social feedback processing (Dekkers, van der Molen, Moor, van der Veen, & van der Molen, 2014; van der Molen, Dekkers, Westenberg, van der Veen, & van der Molen, 2016). Moreover, our preliminary correlations indicated that this task may be useful for examining effects of depression and social anxiety on social feedback processing.…”
supporting
confidence: 70%
“…Following the task, participants complete a self-report measure of task engagement. Our initial pilot study ( N = 19) indicated that an enhanced RewP was observable following social acceptance feedback, a pattern that has also been observed in adult studies of social feedback processing (Dekkers, van der Molen, Moor, van der Veen, & van der Molen, 2014; van der Molen, Dekkers, Westenberg, van der Veen, & van der Molen, 2016). Moreover, our preliminary correlations indicated that this task may be useful for examining effects of depression and social anxiety on social feedback processing.…”
supporting
confidence: 70%
“…That is, the FRN is larger in amplitude for feedback that is incongruent with individuals' prior expectancies about the feedback outcome. Although it has been frequently observed that the FRN is larger for feedback that is worse than expected (Gehring & Willoughby, 2002), our two previous ERP studies revealed that FRN was larger for unexpected vs. expected feedback in the SJP (Dekkers, Van der Molen, Gunther Moor, Van der Veen, & Van der Molen, 2015;. It should be acknowledged, however, that these ERP analyses did not capture all relevant information that is contained in the EEG.…”
Section: Introductioncontrasting
confidence: 60%
“…Thereby, effects of social evaluation (acceptance vs. rejection) and expectancy (expected vs. unexpected outcomes) were manipulated. Early feedback evaluation (FRN component) was mostly sensitive to expectancy violations (Dekkers, Van Der Molen, Gunther Moor, Van Der Veen, & Van Der Molen, 2015; Van Der Molen, Dekkers, Westenberg, Van Der Veen, & Van Der Molen, 2016;Van Der Veen, Van Der Molen, Van Der Molen, & Franken, 2016), while later ERP processing stages (P300 component) reflected expected acceptance judgements (Van Der Veen, Van Der Molen, Sahibdin, & Franken, 2014; or general expectancy effects (Dekkers et al, 2015). In task versions that omitted the expectancy manipulation, early feedback evaluation was also reflecting acceptance vs. rejection judgements (Kujawa et al, 2014;Sun & Yu, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Concerning stimulus complexity, we had no directional hypothesis. We further hypothesized that P300 amplitudes would be sensitive to feedback valence and social dimension (Bellebaum & Daum, 2008;Dekkers et al, 2015;Pfabigan et al, 2015;Van Der Veen et al, 2014. Larger P300 amplitudes were expected after positive compared to negative, and after social compared to non-social feedback.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation